Dynamic Behavior of Ropeway String. Issue 1 (December 2020) - Jena, Shakti P; Ibrahim, Mohd; Subbaratnam, B.; Naresh Kumar, S
Abstract: In this paper a new approach for dynamic behavior of a string is aimed to study lateral vibrations induced in an elastic ropeway string. We are going to deal with the dynamic behavior of a string. In hilly areas we have problem for traveling from one place to another place. There we are using a rope drive system using a string as a rope. A ropeway is a type of maritime lifting gadget used to move light stores and hardware across waterways. Here, multiple ropeways are designed by using solid works and then analyzing with static, transient and dynamic boundary conditions. To suggest optimum materials for optimum ropeway string, 4 materials were chosen (SAE 1020, SAE1137, Al-l7075, Al- 7475) to analyze and study the dynamic behavior of ropeway string by knowing each material results, comparing with each other material results and then showing suitable tables and graphs, finally concluding thesis with optimum material with optimum ropeway string to improve the performance and their durability.